KATEKESE BAGI KELUARGA YANG MENGALAMI HUBUNGAN JARAK JAUH - Wijaya, Albert I Ketut Deni (CREDENDUM: Jurnal Pendidikan Agama, 2019)
Globalization has had an impact on the development of family life. Parents sometmes must leave the family to work. This situation seems to cause problems in children's education and the harmony of familiy. Faced with this situation, contextual catechesis needs to be pursued that is able to help Christian families, epecially in children's education. The catechetical themes that can be given about living a marriage promise, children's education, and building harmony through effective communication. This paper is a study of the results of research on Christian families who experience long-distance relationships. The research was conducted by Nathalia Dwi Oetari (2017), Yosep Subiantoro (2017) and Munika Yudha Dwi Viskana (2018). Based on the results of the research conducted, found various facts related to challenges for families who experience long-distance relationships. This kind of communication in the family is difficult. Communication between family members can only be done through means of communication or social media, and even then if one of them is not working or doing activities